Pairing phylogenetic and metabolic proxy in a rapid radiation : the sea fans Pacifigorgia (Gorgoniidae: Octocorallia) (2017)
After the closure of the Isthmus of Panama, changes in productivity opened new ecological opportunities. This allowed benthic suspension feeders, at the Tropical Eastern Pacific (TEP), to thrive. In this environment, octocoral genera such as Leptogorgia, Muricea and Pacifigorgia coexist. Furthermore, Pacifigorgia is a complex genus, where its species exhibit high morphological diversity with little and conflictive genetic divergence. Our hypothesis is that the closure of the Isthmus of Panama provided novel feeding opportunities to the local organisms at the Colombian TEP. Suspension feeder, like Pacifigorgia, could have used different feeding strategies to exploit the new environmental offer. Consequentially few ancestral Pacifigorgia species could develop different mesh characteristics to optimize their surface-volume ratio obtaining a diverse array of carbon sources while they were in sympatry. After generations this turned into 34 species by likely rapid adaptive radiation processes. Also, it is suggested that sea fans are using different strategies to meet their energetic demands...